Hyperuricemia is a Risk Factor for One-Year Overall Survival in Elderly Female Patients with Acute Coronary Syndrome - Shi Tai; Xuping Li; Zhaowei Zhu; Liang Tang; Hui Yang; Liyao Fu; Xinqun Hu; Zhenfei Fang; Shenghua Zhou (Cardiovascular Therapeutics)
Background. Hyperuricemia is a risk factor for cardiovascular diseases, but the impact of hyperuricemia and sex-related disparities is not fully clear in elderly patients with acute coronary syndrome (ACS). Objective. To investigate the association between hyperuricemia and 1-year all-cause mortality in elderly patients with ACS. Methods. This retrospective cohort study included 711 consecutive ACS patients aged ≥75 years, hospitalized in our center between January 2013 and December 2017. Serum uric acid (sUA), in-hospital events, and 1-year follow-up were analyzed. Multivariable logistic regression models were used to explore the risk factors for in-hospital events and 1-year all-cause mortality. Results. sUA levels were higher in males than in females (381.4 ± 110.1 vs. 349.3 ± 119.1 μmol/l, P<0.001). Prevalence of hypertension (80.5% vs. 72.6%, P=0.020), atrial fibrillation (16.2% vs. 9.5%, P=0.008), and severe heart failure (61.0% vs. 44.2%, P<0.001) were higher in patients with hyperuricemia than in patients with normal sUA. During the 1-year follow-up, 135 patients died (19.0%); all-cause mortality was higher in patients with hyperuricemia than in patients with normal sUA (23.1% vs. 16.7%, P=0.039). Hyperuricemia is related to in-hospital ventricular tachycardia and 1-year all-cause mortality (OR = 1.799, 95% CI 1.050–3.081, P=0.033; OR = 1.512, 95% CI 1.028–2.225, P=0.036, respectively). Multivariable regression analysis models showed that hyperuricemia was an independent risk factor of 1-year all-cause mortality in women (OR = 2.539, 95% CI 1.001–6.453, P=0.050), but not in men (OR = 0.931, 95% CI 0.466–1.858, P=0.839) after adjustment for confounding variables. Conclusions. Hyperuricemia is an independent risk factor for 1-year all-cause mortality in elderly female patients with ACS.